"What Came Out of a Morphological Measurement in The Holy Quran «Al-Tahrir wa Al-Tanwir by Ibn Ashour Al-Tunisi as a Sample»" - Ridha Al- Hiti, Qusay Jaddoa (Journal of Tikrit University for Humanities, 2020)
The present study deals with a morphological issue, mentioned by the ancients and modern scholars. It is summarized by what the research called "what came out of a morphological measurement in the Holy Quran". The study was carried out from the point of application and selection in a great interpretation of a great scientist, whom scholars of credit and charity witnessed to him, that is Ibn Ashour Al-Tunisi in his book “Al-Tahrir wa Al-Tanwir”. The researcher selected words that were mentioned in the interpretation, and they were studied in terms of revealing their morphological origin and explaining their reasons, especially because it violated the steady measurement in the Arabic language.